Self-Awareness Creates Job Satisfaction in PT Indosat, Tbk., Jakarta - Kartini Ismono (Jurnal Administrasi dan Kesekretarisan, 2020)
Job satisfaction is a positive feeling about one's work which is the result of an evaluation of its characteristics. High job satisfaction has positive feelings about her job, while a dissatisfied person has negative feelings about her work. When there is a conversation between technicians, what is often discussed is the satisfaction of his work. The existence of a fact that satisfied technicians are much more productive when compared to dissatisfied technicians has become an irrefutable reason in the day-to-day work activities. PT Indosat, Tbk. referred to in this study is a telecommunications company for international public, and is a form of Foreign Investment (PMA / private) since 1967, which was originally managed by PT Telkom. At that time, PT Indosat, Tbk. is one of the pioneers of Foreign Investment business established to accelerate the recovery of the national economy. Quantitative Descriptive Method is used in this research as a problem-solving procedure by describing the state of the research object at a certain moment (as it is), or research activity on the aspect (variable) studied with 2 (two) variables using simple calculation, namely self-awareness and job satisfaction. Based on the calculation results obtained py = 0.238 with t = 2.586, while the value ttable = 1.99 (a = 0.05, dk = 80), because tcount> ttable (a = 0.05), Ho is rejected and H1 accepted, which means the coefficient of Self Awareness (X) on Job Satisfaction (Y) significant. This finding means that Self Awareness has a direct positive effect on Job Satisfaction, in other words an increase in Self Awareness will lead to improvement in the quality of Job Satisfaction.